Sistem Proteksi Petir Eksternal Pada Gedung Baru Fakultas Teknik Universitas Riau - Hotdin Peterson A; Fri Murdiya (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The new building of Engineering Faculty at Riau University is one of the development planning that was by Riau University. It needs external lightning protection system to protect the building from direct lightning strike. For the protection, it has been designed an external protection system using the method of collecting volume. From the result of the calculation of external protection system with the angle of 0° and the peak current of lighting 60 kA, it was found out that the distance of the strike was rs123,58 m , the value of radius lighting protection was Δmax was 72,6 m, the value of collecting volume was Vcoll 1059990,46 m3 , and the value of lighting protection zones was 0s 76,82° .Keywords : lightning protection system,collection volume method